An Evaluation of Eggshell Waste/Waste Paper Mechanical Properties as Composite Paper - Abdullah, Mohammad; Kum Yoke, Soo; Nuruddin Azlan Raofuddin, Danial; Zaki Sukor, Mohd; Roslan, Azmi; Mariam Mohamad Ilyas, Siti; Hanafie Yasin, Mohd (International Journal of Engineering and Technology, 2018)
Paper as a material, is useful. For this reason, the paper industry has contributed widely to the economy. This is also true for advancement in the technology for recycled papers. Paper fibre or paper pulp however is depleting due to extensive deforestation and loggings which in turn leads to problems such as global warming. Further, eggshell waste is a material found to be useful to produce papers. As such, this study intends to find out the possibilities of using eggshell waste and waste papers to produce papers. To carry out the research, the optimum ratio of fibre in the paper pulp was determined by the maximum strength of recycled paper produced. Eggshell waste was collected from a food court. The eggshells were then separated from their membrane, dried in the sun and grinded. It was then mixed with paper pulp according to the measured ratio. The study found that paper from a combination of eggshell fibre waste against waste paper was able to be produced and the optimum ratio was 2:8 because it had the highest tensile strength. The eggshell waste can be used as a material that enhanced the mechanical properties of recycled paper.Â